Faster, better, cheaper space exploration. - Marcopulos, T. (IEEE spectrum)
For cost and quality reasons, NASA is allowing its contractors great leeway in designing and building new systems. Here, the author describes how this hands-off approach worked when Hewlett-Packard built the electrical ground support system for the Lunar Prospector, which will mark Earth's return to the Moon after 25 years